Experiment and simulation of ELM in NBI heated plasma on EAST tokamak. (21st April 2021) - Geng, K.N.; Tang, T.F.; Kong, D.F.; Zhang, S.B.; Zhang, T.; Huang, C.B.; Wu, M.Q.; Jiang, D.; Lyu, B.; Wang, L.; Gao, W.; Liu, Z.X.; et al.
Abstract: By scanning toroidal rotation with a combination of co- and counter-current direction neutral beam injection (NBI) on the Experimental Advanced Superconducting Tokamak, it is found the size of edge localized mode (ELM) decreases with increasing toroidal rotation in counter-current direction. The synergistic effect of plasma rotation and collisionality on ELM behavior is also studied by statistical analysis. Three-field module in BOUT++ framework is employed to study the impacts of toroidal rotation/ E × B flow shear on ELM behaviors. The BOUT++ simulation results show that both Co- and Ctr-NBI induced net flow have stabilization effects on the peeling-ballooning modes, especially for counter NBI case, high- n ballooning mode can be totally stabilized. With larger E × B shear, the mode number of most unstable mode downshifts in the counter NBI case, with larger E × B shear, the mode number of most downshifts in the counter NBI case, correlated with reduced ELM size.